1996
DOI: 10.1002/(sici)1096-8628(19961218)66:3<320::aid-ajmg16>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of holoprosencephaly and arhinencephaly in metropolitan Atlanta, 1968–1992

Abstract: We report the descriptive epidemiology of holoprosencephaly and arhinencephaly using data from the Metropolitan Atlanta Congenital Defects Program, a population-based birth defects surveillance system with multiple sources of ascertainment. From 1968-1992, we ascertained 63 cases of holoprosencephaly and arhinencephaly from approximately 734,000 births, for a birth prevalence of 0.86 per 10,000. Thirteen case infants with holoprosencephaly and four case infants with arhinencephaly were categorized as having sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
65
3
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 40 publications
16
65
3
2
Order By: Relevance
“…This prenatal diagnosis often results in the termination of pregnancy, depending on the severity of disease. The higher incidence of holoprosencephaly among females was previously reported [19,21], and our results also yielded consistent findings, although phenotypic sex was not mentioned in seven cases. The female predominance may be explained by the higher likelihood of males to abort spontaneously [21].…”
Section: Discussionsupporting
confidence: 91%
“…This prenatal diagnosis often results in the termination of pregnancy, depending on the severity of disease. The higher incidence of holoprosencephaly among females was previously reported [19,21], and our results also yielded consistent findings, although phenotypic sex was not mentioned in seven cases. The female predominance may be explained by the higher likelihood of males to abort spontaneously [21].…”
Section: Discussionsupporting
confidence: 91%
“…Non-craniofacial abnormalities can occur in more than half of the cases without chromosomal abnormalities (25). The ratio was similar in our study, 4…”
Section: Italian Regions (5)supporting
confidence: 88%
“…cases were found in a series of 63 patients in the literature (25). The only case associated with maternal diabetes in our series represents a similar ratio despite the small number of cases.…”
Section: Italian Regions (5)supporting
confidence: 73%
See 1 more Smart Citation
“…Rassmussen et al [4] found a birth prevalence of 0.72 cases per 10,000 births in Metropolitan Atlanta from 1968 to 1992. Its incidence is increased 60-fold among studies of aborted human embryos, therefore indicating that most cases are eliminated prenatally [2].…”
Section: Introductionmentioning
confidence: 99%